Respiratory symptoms and ventilatory capacity in swine confinement workers. - Zuskin, E (1992)
A group of 59 workers (41 men and 18 women) employed in swine confinement areas was studied to assess the presence of acute and chronic respiratory symptoms and the prevalence of abnormalities in ventilatory function. A control group of 46 (31 men and 15 women) unexposed workers was studied for the prevalence of chronic respiratory symptoms. For both male and female swine confinement workers complaints of chronic cough, dyspnoea, and chest tightness were significantly more frequent than among control workers. Male workers also complained more of chronic phlegm. Male swine confinement workers who were smokers had significantly higher prevalences of chronic cough, chronic phlegm, and chronic bronchitis than male non-smoking swine confinement workers. The frequency of acute symptoms associated with the workshift was high among the swine confinement workers with more than half of the workers complaining of cough and dyspnoea associated with work. Significant acute across shift reductions in lung function occurred in swine confinement workers, being largest for FEF25. All Monday preshift ventilatory capacity measurements in male confinement workers were significantly lower than predicted values; FVC and FEV1 were found to be lower than predicted values for women. The data indicate that exposure in swine confinement buildings is associated with the development of acute and chronic respiratory symptoms and impairment of lung function. Smoking appears to aggravate these changes.